Mendelian randomization study reveals the effect of idiopathic pulmonary fibrosis on the risk of erectile dysfunction - Zhang, Kun; Zhou, Jiejun; Li, Anqi; Chen, Mingwei (Frontiers in Medicine, 2023)
Background: Several studies have found erectile dysfunction (ED) is associated with interstitial lung disease. However, the causal relationship between idiopathic pulmonary fibrosis (IPF) and ED risk remains unclear. The present two-sample mendelian randomization (MR) study aimed to reveal the causal effect of IPF on ED risk. Methods: This study included two GWAS summary statistics of IPF (1,028 cases and 196,986 controls) and ED (6,175 cases and 217,630 controls) of European ancestry. The inverse-variance weighted (IVW) was applied as the primary method, and MR-Egger, weighted median, weighted mode, and simple mode were applied as complementary methods to estimate the causal impact of IPF on ED risk. The MR-PRESSO global test and MR-Egger regression were applied to evaluate the pleiotropy. The Cochran's Q test was applied to examine heterogeneity. The leave-one-out analysis ensures the robustness and reliability of the results. Results: Twenty-one genetic variants were obtained as IPF instrumental variables without pleiotropy and heterogeneity. MR analysis using the IVW showed a potential causal relationship between IPF and increased ED risk (ORIVW = 1.046, 95% CI: 1.020-1.073, P = 0.001), and consistent results were obtained with MR-Egger, weighted median, and weighted mode. The leave-one-out analysis showed that no instrumental variables unduly influenced the results. Conclusions: This study suggested that IPF may increase the ED risk of the European population.